Estimation of the effects of greenhouse gases generated by wastewater treatment plants located in the basin of the Bogotá River (2019)
The present study contains a data analysis that links the amount of organics in the wastewater treatment plant a in the basin of the Bogotá river and its incidence in the generation of greenhouse gases during the process of depuration. A series of technical consideration regarding the generations of greenhouse gases among different treatment plants are mentioned. Accordingly with the characteristics of the system employed in the wastewater treatment is determined which is the one generating a higher amount of emissions accounting the actual status of each plant. To achieve so, the level 1 methodology of the IPCC for greenhouse emissions is employed. Based on the results is determined which of the treatment systems used in the wastewater treatment plants are producing most of the greenhouse gases emissions.